A revision of the American spider genus Strotarchus Simon, 1888 (Araneae: Dionycha, Systariinae) - Bonaldo, Alexandre B.; Saturnino, Regiane; Ramírez, Martín J.; Brescovit, Antonio D. (Zootaxa, 2012)
The genus Strotarchus Simon, 1888 is characterised for 18 species occurring from United States to Brazil. Seven previouslyknown species are redescribed: S. nebulosus Simon, 1888, the type species; S. praedator (O. Pickard-Cambridge, 1898); S. pis-catorius (Hentz, 1847); S. violaceus F.O. Pickard-Cambridge, 1899; S. minor Banks, 1909; S. tropicus (Mello-Leitão, 1917)and S. planeticus Edwards, 1958. Eleven new species are described: S. monasticus n. sp., S. mazamitla n. sp., S. tamaulipas n.sp., S. tlaloc n. sp., S. jacala n. sp., S. bolero n. sp. and S. michoacan n. sp. from Mexico; S. silvae n. sp. and S. urarina n. sp.from Peru; S. beepbeep n. sp. from United States and S. gandu n. sp. from Brazil. The male of S. minor and the female of S. tropicus are described for the first time.